Special issue : social movements/legal possibilities - Barclay, Scott; Jones, Lynn C.; Marshall, Anna-Maria; Sarat, Austin (Studies in law, politics, and society, 2011)
Social movements provide the engine of legal change and law itself spurs social movement activity. This issue of Studies in Law, Politics and Society examines the legal life of social movements and their impact on law. The articles collected here take up social movements in several different nations, including France, South Africa and Canada, asking us to consider the way context is reflected in movement activities.